Relationships of Microbiome Markers With Extraintestinal, Psychological Distress and Gastrointestinal Symptoms, and Quality of Life in Women With Irritable Bowel Syndrome. Issue 2 (February 2020) - Hollister, Emily B.; Cain, Kevin C.; Shulman, Robert J.; Jarrett, Monica E.; Burr, Robert L.; Ko, Cynthia; Zia, Jasmine; Han, Claire J.; Heitkemper, Margaret M.
Abstract : Introduction: Altered microbial diversity has been associated with gastrointestinal (GI) symptoms in persons with irritable bowel syndrome (IBS). Less is known about the relationship of microbiome with extraintestinal pain and psychological distress symptoms and quality of life (QOL) in persons with IBS. We aimed to evaluate the relationship of fecal microbiota to GI symptoms, stool consistency, psychological distress, extraintestinal pain, and QOL in participants meeting Rome III criteria for IBS. Methods: Seventy-six women completed a 28-day diary that included GI, stool consistency, psychological distress, and extraintestinal pain ratings. Participants completed the IBS-Specific Quality of Life questionnaire. Stool samples were collected and analyzed by 16S rRNA gene sequencing. Principal component analysis was performed and the first 2 components (PC1, PC2) were used to test relationships among bacterial families and clinical measures. Results: Participants were categorized as IBS constipation (n=22), IBS diarrhea (n=39), IBS mixed (n=13), and IBS unsubtyped (n=2). There was a significant group effect for the Firmicutes to Bacteroidetes ratio and PC1. Lower microbial diversity and richness were associated with increased urgency and extraintestinal pain, worse QOL, and looser stools. Lower extraintestinal pain was associated with increased Rikenellaceae, Christensenellaceae, Dehalobabacteriaceae, Oscillospiraceae, Mogibacteriaceae, Ruminococcaceae, Sutterellaceae, Desulfovibrionaceae, and Erysipelotrichaceae abundances. QOL was positively associated with many of these same bacterial families. Higher Firmicutes to Bacteroidetes ratio was positively associated with loose stools. There were no statistically significant relationships between daily psychological distress or abdominal pain and bacterial families. Conclusions: Stool microbial diversity and composition are linked to daily extraintestinal symptoms, stool consistency, and QOL in women with IBS. Abstract : Supplemental Digital Content is available in the text.